Comparative analysis of gene and disease selection in genomic newborn screening studies - Betzler, Isabel R.; Hempel, Maja; Mütze, Ulrike; Kölker, Stefan; Winkler, Eva C.; Dikow, Nicola; Garbade, Sven; Schaaf, Christian P.; Brennenstuhl, Heiko (Journal of inherited metabolic disease, 2024)
Genomic newborn screening (gNBS) is on the horizon given the decreasing costs of sequencing and the advanced understanding of the impact of genetic variants on health and diseases. Key to ongoing gNBS pilot studies is the selection of target diseases and associated genes to be included. In this study, we present a comprehensive analysis of seven published gene-disease lists from gNBS studies, evaluating gene-disease count, composition, group proportions, and ClinGen curations of individual disorders. Despite shared selection criteria, we observe substantial variation in total gene count (median 480, range 237-889) and disease group composition. An intersection was identified for 53 genes, primarily inherited metabolic diseases (83%, 44/53). Each study investigated a subset of exclusive gene-disease pairs, and the total number of exclusive gene-disease pairs was positively correlated with the total number of genes included per study. While most pairs receive “Definitive” or “Strong” ClinGen classifications, some are labeled as “Refuted” (n = 5) or “Disputed” (n = 28), particularly in genetic cardiac diseases. Importantly, 17%-48% of genes lack ClinGen curation. This study underscores the current absence of consensus recommendations for selection criteria for target diseases for gNBS resulting in diversity in proposed gene-disease pairs, their coupling with gene variations and the use of ClinGen curation. Our findings provide crucial insights into the selection of target diseases and accompanying gene variations for future gNBS program, emphasizing the necessity for ongoing collaboration and discussion about criteria harmonization for panel selection to ensure the screening's objectivity, integrity, and broad acceptance.
Veröffentlicht: 16 May 2024
Gesehen am 11.11.2024